Technological advances in prospecting sites for pumped hydro energy storage - Akpoti, Komlavi; Obahoundje, S.; Mortey, E. M.; Diawuo, F. A.; Antwi, E. O.; Gyamfi, S.; Domfeh, M. K.; Kabo-bah, A. T. (Elsevier, 2023)
This chapter provides a survey of pumped hydroelectric energy storage (PHES) in terms of the factors considered in the site selection process: geographic, social, economic, and environmental. Due to the number and complexity of factors considered for this purpose, a multicriteria decision-making model is often used during the selection process. From our study, it is observed that the implementation of a PHES project may come with several environmental concerns, that is land and water requirements, impacts on the fishery industry, aquatic habitat, cultural, historical as well as natural. However, we also observed that many of these concerns are being addressed with improvement in PHES technology.